Perpetrators and Social Death: A Cautionary Tale. (October 2016) - Tirrell, Lynne
Abstract: Understanding evil requires both addressing the grave wrongs done to the victim and addressing the perpetrator who does these wrongs. Claudia Card's concept of social vitality was developed to explain what génocidaires destroy in their victims. This essay brings that concept into conversation with perpetrator testimony, arguing that the génocidaires' desire for their own social vitality, achieved through their destruction of the social world of their targets, in fact boomerangs to corrode the vitality of their own lives. This is true whether they succeed or fail in their genocidal project. Card's recent analysis of "being a badass" is brought to bear on the cultivation of evil, and the essay suggests four strategies for meeting Card's "moral challenge of avoiding evil responses to evil."